Food Insecurity and Conflict : Applying the WDR Framework - Brinkman, Henk-Jan (World Bank, Washington, DC, 2017)
This paper provides a synthetic overview of the link between food insecurity and conflict, addressing both traditional (civil and interstate war) and emerging (regime stability, violent rioting and communal conflict) threats to security and political stability. In addition, it addresses the various attempts by national governments, intergovernmental organizations, and civil society to address food insecurity and, in particular, the link with conflict. It begins with a discussion of the various effects of food insecurity for several types of conflict, and discusses the interactions among political, social, and demographic factors that may exacerbate these effects. It then discusses the capabilities of states, international markets, intergovernmental organizations, and nongovernmental organizations (NGOs) to break the link between food security and conflict by focusing on mechanisms that can shield both food consumers and producers from short-term price instability. Finally, it discusses projected trends in both food insecurity and conflict and concludes with some brief comments on policies that can build resilience in light of projections of higher and volatile food prices and a changing climate.